Students’ Learning Approach in SMK Negeri 1 Singaraja in The EFL Online Learning Context - Damayanti, Putu Vergi; Santosa, Made Hery; Myartawan, I Putu Ngurah Wage (Journal of Educational Study, 2023)
This study investigated the learning approach of tenth-grade students in SMK Negeri 1 Singaraja in the EFL online learning context. The study employed quantitative research. The sample involves 89 students in tenth grade in the Hotel Accommodation program. This study used the R-SPQ-2F questionnaire which was modified for the online learning context. The data analysis was implemented in the R-SPQ-2F questionnaire mean score analysis. The results showed that tenth-grade students in SMK Negeri 1 Singaraja tend to surface approach (tsap= 29.55 > tdap= 28.32). It is suggested students will study in-depth to build meaningful learning by understanding concepts and developing potential optimally in the implication of learning English as a foreign language in the online learning context.